1982
DOI: 10.1017/s1446788700024976
|View full text |Cite
|
Sign up to set email alerts
|

A limit theorem for the tails of discrete infinitely divisible laws with applications to fluctuation theory

Abstract: Suppose that (/>") is an infinitely divisible distribution on the non-negative integers having Levy measure (v n ). In this paper we derive a necessary and sufficient condition for the existence of the limit lim ; , -ooPn/"n-We also derive some other results on the asymptotic behaviour of the sequence (p n ) and apply some of our results to the theory of fluctuations of random walks. We obtain a necessary and sufficient condition for the first positive ladder epoch to belong to the domain of attraction of a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…increments and assume that S n → −∞ a.s. Then an analogue of τ x is the stopping time ν x = min{n ≥ 1 : S n < −x}. Asymptotics for ν x have been studied in [12] for x = 0, and in [10], [6] for x > 0. In [12], it is shown that P{ν 0 > n} ∼ P{S n ≥ 0}/n if the latter is a subexponential sequence (see definition below).…”
Section: Theorem 481]) Says That X T → −∞ If and Only Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…increments and assume that S n → −∞ a.s. Then an analogue of τ x is the stopping time ν x = min{n ≥ 1 : S n < −x}. Asymptotics for ν x have been studied in [12] for x = 0, and in [10], [6] for x > 0. In [12], it is shown that P{ν 0 > n} ∼ P{S n ≥ 0}/n if the latter is a subexponential sequence (see definition below).…”
Section: Theorem 481]) Says That X T → −∞ If and Only Ifmentioning
confidence: 99%
“…Asymptotics for ν x have been studied in [12] for x = 0, and in [10], [6] for x > 0. In [12], it is shown that P{ν 0 > n} ∼ P{S n ≥ 0}/n if the latter is a subexponential sequence (see definition below). In [10] and [6], the asymptotics for ν x have been found when x > 0.…”
Section: Theorem 481]) Says That X T → −∞ If and Only Ifmentioning
confidence: 99%
“…The situation when Eτ < ∞, which is a particular case of the relative stability, was considered by Embrechts and Hawkes [5]. There it has been shown that If the expectation EX is finite, then the condition ∞ k=1 k −1 P(S k ≤ 0) = ∞ is equivalent to the inequality EX ≤ 0, see again [19,Theorem 17.1].…”
Section: 1mentioning
confidence: 99%
“…:In (nPn )-1--+ 00 as n --+ 00 • As in Embrechts and Hawkes (1982), we have that LC n is absolutely convergent, LC n =0 and c n ---qn ,(n _(0). It follows from (3.3) and (3.4) that…”
Section: The Levy Measure Of Glsdmentioning
confidence: 76%
“…We will therefore concentrate on asymptotic expressions for CY n as 11 _ 00. The following theorem of Embrechts and Hawkes (1982) illustrates that such expressions are closely related to the convolution behavior of Pn as n _ 00.…”
Section: Introduction the Generalized Logarithmic Series Distributionmentioning
confidence: 93%